Word-based versus root-based morphology in the African languages - Posthumus, L. C. (South African Journal of African Languages, 1994)
The study of morphology has been sadly neglected in recent years, primarily because morphology had not been recognized as a separate level of linguistic study within the Transformational Generative framework. An investigation into the treatment of morphology in the African languages reveals a lack of consistency. The problem of the appropriate base-form for morphological analysis is addressed in this article. Many linguists have argued that a universal approach to morphology is not feasible. The appropriate approach is determined by the nature of the morphology of the language under investigation. This article is an investigation into the applicability of either the word-based or the root-based morphology to the African languages. The linguistic conséquences of the application of these two approaches are discussed in some detail.